EFECTIVITY MINOXIDIL AS A TREATMENT OF ALOPECIA AREATA - Wayan Evie Frida Yustin (Universitas Udayana, 2013)
Alopecia areata is hair loss with patchy formation, the most common cause of alopecia nonscarring. Occurred in 1,7 % of Americans aged 50 years. Can occurs in both sexes, all races and any age. Genetic and immunological factors play an important role as a cause of Alopecia areata. The clinical features alopecia areata are round or oval lesions, total baldness, smoothness on the scalp or other parts of the body that has hair. Minoxidil is one of the effective therapy for Alopecia areata. Known for more than 30 years of minoxidil to stimulate hair growth. Minoxidil works on hair follicles, opening the potassium channels, and have vascular effects that can increase blood flow to hair. Histological studies showed that minoxidil therapy may increase the proportion hair follicles in anagen phase and decrease hair follicles at telogen phase. Minoxidil through sulphat metabolites can open potassium channels, the opening potassium channels can increase the hair follicles growth. The study of the effects minoxidil on human epidermal keratinocytes and hair follicles with different culture conditions and markers proliferation, found that minoxidil with micro molar concentration can stimulate proliferation both type of cells and all culture condition, whereas minoxidil with milimolar concentration will inhibit cell growth. In addition, several studies have also reported an association minoxidil to vascular effect and stimulating VEGF can promote the increase hair follicle